The Effect of Human Resources and Financial Administration Budget Absorption in Higher Education Institutions in Islamic Perspectives - Ibnu Hasan; Sardimi Sardimi; Nurul Wahdah (Iqtishodia: Jurnal Ekonomi Syariah, 2023)
Budget absorption is a government instrument through fiscal policies in moving the economic wheels. The government expenditure sector aims at supporting community welfare development. Budget absorption per quarter at the IAIN Palangka Raya is in slow category. The research aims to identify the effect of human resources and financial administrative on budget absorption at the IAIN Palangka Raya. The research is a quantitative research with multivariate correlation approach. Population of the research includes stakeholders who handle the budget at the IAIN Palangka Raya. The research sample consists of 27 respondents. Data collection carries out through questionnaires and documents. Data resulted from the questionnaires are analyzed using multiple linear regression analysis. The research results indicate that human resources (HR) and financial administration have no effect on budget absorption with bootstrapping value of 0.597 and 0.480, respectively. The results suggest that the level of human resources and financial administration has no effect on budget absorption at the IAIN Palangka Raya